Actinide–lanthanide co-extraction by rigidified diglycolamides. Issue 1 (2nd January 2018) - Macerata, Elena; Ossola, Annalisa; Panzeri, Walter; Giola, Marco; Faroldi, Federica; Tinonin, Dario Alberto; Mele, Andrea; Casnati, Alessandro; Mariani, Mario
ABSTRACT: Within the actinide and lanthanide co-extraction strategy, three rigidified diglycolamides, namely 2, 6-bis ( N -dodecyl-carboxamide)-4-oxo-4 H -pyran (1 ), 2, 6-bis-[ N -(4- tert -butylphenyl)carboxamide]-4-oxo-4 H -pyran (2 ), 2, 6-​bis[( N -docecyl- N -methyl)carboxamide]-​4-methoxy-​tetrahydro-pyran (3 ), were synthesized. Moreover, the effect of structural rigidification on Am(III) and Eu(III) extraction under different conditions was investigated. The carboxamide extractant3 resembles the extracting behavior of N, N, N ′, N ′‐tetraoctyl diglycolamide (TODGA) in terms of efficiency and affinity within the lanthanide family, together with fast kinetics and satisfactory cation back-extraction. The presence of 1-octanol in the diluent mixture strongly affects the ligand stability. Moreover, despite the low extraction efficiency showed by1 and2, all the three ligands exhibit a higher affinity for Am with respect to TODGA, resulting in a lower lanthanide/Americium separation factor, of around 4 for ligand3 and close to 1 for ligands1 and2 .